2015
DOI: 10.1103/physrevb.92.134402
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic structure of the quasi-one-dimensionalLa3OsO7as determined by neutron powder diffraction

Abstract: Insulating 5d3 La 3 OsO 7 and the isostructural hole-doped analog La 2.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The Ca-doped La 3 OsO 7 was also studied. Despite the change of nominal carrier density, surprisingly, this hope-doped system remain an insulator (or a semiconductor), violating the rigid band scenario [16]. Similar robust insulating behavior was also found in some doped iridates [17,18], which was expected to show superconductivity after doping [19,10].…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…The Ca-doped La 3 OsO 7 was also studied. Despite the change of nominal carrier density, surprisingly, this hope-doped system remain an insulator (or a semiconductor), violating the rigid band scenario [16]. Similar robust insulating behavior was also found in some doped iridates [17,18], which was expected to show superconductivity after doping [19,10].…”
Section: Introductionmentioning
confidence: 73%
“…It is found that U eff (Ru)=1 eV is the best choice to reproduce the experimental structure of La 3 RuO 7 , while for La 3 OsO 7 the bare GGA without U eff is the best choice. Comparing with experimental values [16,20], the deviation of calculated lattice constants are only < 0.8% for La 3 OsO 7 , and 0.5% for La 3 RuO 7 , providing a good start point to study other physical properties. These choices of U eff are quite reasonable considering the gradually deceasing Hubbard repulsion from 3d to 5d.…”
Section: Model and Methodsmentioning
confidence: 98%
See 3 more Smart Citations